Clostridium difficile in retail chicken meat parts and liver in the Eastern Region of Turkey - Guran, Husnu Sahan; Ilhak, Osman Irfan (Springer International Publishing Ag, 2015)
In recent studies, the presence of Clostridium difficile has been shown in foods and animals that may be a source of infection in susceptible humans. In the present study, it was aimed to investigate the prevalence of toxigenic Clostridium difficile spores and vegetative cells in chicken meat parts and liver. For this purpose, 310 samples (75 leg quarters, 75 breast, 60 wings, 60 drumsticks and 40 chicken livers) were collected from two cities in eastern region of Turkey for 6 months and analyzed for the presence of C. difficile. C. difficile was isolated from 25 (8.06 %) of 310 samples. The prevalence of C. difficile was 12, 8, 6.6, 5 and 7.5 % for the leg quarter, breast, wing, drumstick and liver, respectively. The results showed that the prevalence of C. difficile in chicken samples was higher in winter months (December, January and February). Multiplex PCR results showed that 5 of 25 C. difficile isolates had toxin B (tcdB) gene, and 8 isolates had toxin A (tcdA) gene. None of the isolates was having binary toxin (cdtA or cdtB) genes. The findings of the present study show that toxigenic C. difficile spores can be found in both chicken meat parts and in livers although their numbers is low.
Keywords: Chicken; Clostridium difficile; Spores; Toxinotype; Multiplex PCR